Multi-modal fusion of in-situ video data and process parameters for online forecasting of cookie drying readiness - Shichen Li; Hao Feng; Chenhui Shao (Journal of Food Engineering, 2027)

Simultaneously achieving high sensitivity and long-term chromatic stability in anthocyanin-loaded PVA/chitosan nanofibers for real-time food spoilage monitoring - Faizan E. Mustafa; Shichen Li; Bong-Kee Lee (Food Research International, 2026)

Multi-shelled hollow architecture enabling synergistic multi-transportation pathway for Li+ in composite quasi-solid electrolyte - Lili Lan; Xinhong Qi; Xiongbin Yang; Shichen Zhang; Yihang Li; Lu Gao; Xiaobin Jiang; Xiangcun Li; Gaohong He (Chemical Engineering Journal, 2026)

Diversified cropping combined with nutrient optimization regulates microbial resource limitations, thereby influencing ecoenzymatic carbon and nitrogen use efficiencies - Wei Zhang; Wanting Li; Zhuolin Li; Xinlei Li; Ruqi Duan; Dexiang Luo; Guohui Xiong; Mingmin Li; Jun Tao; Shichen Li; Yingfen Yang; Zhengxiong Zhao (Agriculture, Ecosystems & Environment, 2026)

Environmental and ecosystem economic benefits of optimized nitrogen management for tobacco production in subtropical region - Zhi Yao; Zheng Yuan; Guisu Zhou; Xingbang Wang; Liangjun Yu; Shichen Li; Zhengxiong Zhao (Environment, Development and Sustainability, 2026)

Exploring the spatial impact of China's government-led tourism development model on vernacular architecture in a traditional village - Peiyan Li; Kojiro Sho; P. Monica Chien; Shichen Zhao (Journal of Rural Studies, 2026)

Predictive Multi-Physics coupling coal combustion model under rapid heating - Hanjian Li; Ying Zhao; Shichen Ding; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Huanying Chi (Fuel, 2026)

Mechanistic insights into selective Pb(II) removal by magnetic sludge-derived biochar: A combined experimental and DFT study - Ermao Ding; Shichen Wang; Ke Zhao; Xiang Li; Zuoping Zhao (Journal of Environmental Management, 2026)

Effect of CO2 and H2O on pyrolysis characteristics and structural evolution of Zhundong coal under rapid heating rate - Huanying Chi; Shichen Ding; Ying Zhao; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Hanjian Li (Fuel, 2026)

A bHLH transcription factor negatively regulates effective panicle number and grain yield by modulating auxin transport and distribution in rice - Tao Yang; Rui Zhu; Jinlong Li; Yulong Wang; Lei Zhou; Qiaoqiao Zhao; Ningjia Jiang; An Zeng; Yanli Qin; Haixia Liu; Chenyu Xia; Shichen Han; et al. (Molecular Plant, 2026)

Overcoming the sensitivity–stability trade-off in colorimetric food sensors using immersion-electrospun natural anthocyanin-loaded PCL/PVP membrane - Shichen Li; Faizan E Mustafa; Bong-Kee Lee (Food Chemistry, 2026)

Optimizing soil health and maize yield in continuous cropping: synergistic effects of long-term straw return and winter land-use - Guiru ZHAO; Shichen LI; Chunhe JIANG; Xiaoyao DING; Feng ZHOU; Kaixian WU; Bozhi WU; Michael FULLEN (Pedosphere, 2026)

Carbon sequestration potentials in paddy soil: Rice straw phytolith and phytolith carbon with protozoa abundance - Tianyi Shi; Pan Zhou; Wenyuan Wang; Chunyu Hou; Mei Han; Xuming Pan; Liangzi Cao; Jianye Li; Shichen Sun; Li Wang; Duu-Jong Lee (Bioresource Technology Reports, 2025)

Application of voltage to enrich anaerobic ammonium-oxidizing bacteria from mixed cultures for the degradation of actual wastewater containing COD - Yongqiang Zhu; Zhiguang Chang; Zhiling Li; Zhenxin Li; Shichen Kang; Minli Zhang (Environmental Monitoring and Assessment, 2025)

The RLI1–OsPUB77–OsBZR3 module mediates the crosstalk between phosphate starvation and brassinosteroid signaling pathways to shape rice shoot architecture - Kai Wang; Peng Yan; Jiangfan Guo; Wei Li; Shichen Zhou; Yijian Liu; Jiming Xu; Yu Liu; Yunrong Wu; Zhongchang Wu; Peng Wang; Chuanzao Mao; et al. (Molecular Plant, 2025)

Experimental and numerical study on flashing jet characteristics in the leakage process of hazardous liquefied gas - Yangshuo Dong; He Liu; Yu Guan; Shichen Tu; Jihai Duan; Chaojie Li (Fuel, 2025)

Hofmeister effect-assisted chain bundling and limited coalescence in Pickering emulsion to construct tough and conductive scaffolds for bone regeneration - Huan Tan; Linlong Li; Xue Bai; Yu Deng; Shichen Hu; Yuanyuan Zhou; Shirun Chu; Zili Guo; Jiahao Zhang; Hua Li; Jie Weng (Chemical Engineering Journal, 2025)

Attribution analysis of ambient temperature on hospitalization burden of multiple system diseases in a subtropical monsoon climate city in China - Yanlu Li; Xubiao Duan; Shichen Wan; Jinyun Zhu; Yanbin Hao (International Journal of Biometeorology, 2025)

Uncertainty-aware constrained optimization for air convective drying of thin apple slices using machine-learning-based response surface methodology - Shichen Li; Amir Malvandi; Hao Feng; Chenhui Shao (Journal of Food Engineering, 2025)

Associations of physical frailty and polygenic score with incident heart failure in cardiovascular patients: unraveling the mediating role of inflammation - Jiajin Chen; Sicheng Li; Shichen Bu; Xiaoqing Nie; Le Zhang; Lingjun Jie; Ya Fang; Cuilian Dai; Yan Wang (GeroScience, 2025)

Genome-Wide Identification and Expression Analysis of the STAT Family in Reeve’s Turtle (Mauremys reevesii) - Yi Song; Zeshuo Zhou; Shichen Huang; Zhiyuan Li; Xuechi Zhu; Hongming Zhou; Yuxin Jiang; Duminda S. B. Dissanayake; Arthur Georges; Lei Xiong (Biochemical Genetics, 2025)
The Stat (signal transducer and activator of transcription) gene family plays a vital role in regulating immunity and the processes of cellular proliferation, differentiation, and apoptosis across diverse organisms. Although the functions of Stat genes in immunity have been extensively documented in many mammals, limited data are available for reptiles. We used phylogenetic analysis to identify eight putative members of the Stat family ( Stat1-1 , Stat1-2 , Stat2 , Stat3 , Stat4 , Stat5b , Stat6-1 , and Stat6-2 ) within the genome of M. reevesii , a freshwater turtle found in East Asia. Sequence analysis showed that the Stat genes contain four conserved structural domains protein interaction domain, coiled-coil domain, DNA-binding domain, and Src homology domain 2. In addition, Stat1 , Stat2 , and Stat6 contain TAZ2bind, Apolipo_F, and TALPID3 structural domains. The mRNA levels of Stat genes were upregulated in spleen tissues at 4, 8, 12, and 16 h after administration of lipopolysaccharide, a potent activator of the immune system. Stat5b expression at 12-h LPS post-injection exhibited the most substantial difference from the control. The expression of Stat5b in spleen tissue cellular was verified by immunofluorescence. These results suggest that Stat5b plays a role in the immune response of M. reevesii and may prove to be as a positive marker of an immune response in future studies.

Application of sponge iron-carbon to enrich anaerobic ammonia-oxidizing bacteria from sludge mixture and coupled denitrification for degradation of industrial wastewater - Zhenxin Li; Yongqiang Zhu; Minli Zhang; Zhiling Li; Zhiguang Chang; Shichen Kang (Journal of Contaminant Hydrology, 2025)

Resource utilization of microcrystalline magnesite: Synthesis of magnesium oxide by malic acid steam-assisted decomposition method for the synergetic adsorption of Congo red dye and Cu(II) ion - Jun Li; Ziyu Zhang; Rongzheng Gao; Xiaohui Li; Guoheng Sun; Ziye Zhou; Runtang Feng; Heqi Qi; Dong Zhang; Zihan Zhao; Shichen Xing; Dongmo Wu; et al. (Environmental Research, 2025)

Metal organic frameworks intensify lithium ion conduction and SEI formation inlayed in solid electrolyte facing with lithium metal anode - Shichen Zhang; Yihang Li; Jinzhong Liu; Xiongbin Yang; Xinhong Qi; Xiangcun Li; Gaohong He (Chemical Engineering Journal, 2025)

Enhanced anaerobic bioremediation of oil-contaminated intertidal sediment with a combination of anaerobically-synthesized rhamnolipids and sulfate - Lijia Jiang; Qian Hao; Shichen Li; Shidi Jin; Edidiong Okokon Atakpa; Yinghui Ma; Chunfang Zhang; Haitao Ding (Environmental Pollution, 2025)

Effectiveness of horizontal air curtains in reducing buoyancy-driven heat flux: Insights from small-scale saltwater experiments - Yanlei Yu; Yunfei Xia; Yukun Xu; Lianjie He; Shichen Li; Jun Gao (Building and Environment, 2025)

Characterizing Holocene environmental transitions using magnetic properties of sediments from the continental shelf of the northern South China Sea - Yi Wu; Guanqiang Cai; Shun Li; Shixun Wang; Shuqing Fu; Yulin Han; Shichen Tao (Marine Geology, 2025)

Unraveling the role of pyrolysis temperature in biochar-mediated modulation of soil microbial communities and tobacco bacterial wilt disease - Shichen Li; Linyuan Yang; Tao Jiang; Waqar Ahmed; Fupeng Mei; Jinhao Zhang; Tao Zhang; Yingfen Yang; Xiaoci Peng; Qu Shan; Dexiang Luo; Zhengxiong Zhao (Applied Soil Ecology, 2025)

Mesoporous dual-atom nanozyme induced cuproptosis and apoptosis for boosting immunogenic cell death along with reprogramming tumor immune-suppressive microenvironment - Yunhao Wang; Lei Ding; Ziguo Lin; Baolong Li; Di Hu; Shichen Zhang; Shujun Zhou; Yuxiang Ning; Fei Xin; Yunfei Ying; Fukai Zhu; Peiyuan Wang; et al. (Chemical Engineering Journal, 2025)

Nanofiber connected metal organic frameworks adsorption membrane to enhance Li+ conduction and alleviate interfacial side reaction for solid electrolyte - Xinhong Qi; Yihang Li; Shichen Zhang; Xiangcun Li; Xuri Wang; Helong Jiang; Xuemei Wu; Xuehua Ruan; Xiaobin Jiang; Gaohong He; Jiangping Tu (Chemical Engineering Journal, 2024)

Cooking-related thermal comfort and carbon emissions assessment: Comparison between electric and gas cooking in air-conditioned kitchens - Jiajun Li; Shichen Li; Yingqi Zeng; Xiang Zhou; Lingjie Zeng; Meng Liu; Changsheng Cao; Yunfei Xia; Jun Gao (Building and Environment, 2024)

Changes in soil microbial community and function across stand age of Cryptomeria japonica var. sinensis plantations in subtropical China - Li Zhang; Shichen Xiong; Ya Shen; Chengming You; Han Li; Lixia Wang; Sining Liu; Bo Tan; Hongwei Xu; Lin Xu; Jiao Li; Zhenfeng Xu (Applied Soil Ecology, 2024)

The OsNAC41-RoLe1-OsAGAP module promotes root development and drought resistance in upland rice - Shichen Han; Yulong Wang; Yingxiu Li; Rui Zhu; Yunsong Gu; Jin Li; Haifeng Guo; Wei Ye; Hafiz Ghualm Nabi; Tao Yang; Yanming Wang; Pengli Liu; et al. (Molecular Plant, 2024)

A genetic algorithm with critical path-based variable neighborhood search for distributed assembly job shop scheduling problem - Shichen Tian; Chunjiang Zhang; Jiaxin Fan; Xinyu Li; Liang Gao (Swarm and Evolutionary Computation, 2024)

Curcumin induces mitophagy by promoting mitochondrial succinate dehydrogenase activity and sensitizes human papillary thyroid carcinoma BCPAP cells to radioiodine treatment - Li Zhang; Ling Qiu; Shichen Xu; Xian Cheng; Jing Wu; Yunping Wang; Wenjing Gao; Jiandong Bao; Huixin Yu (Toxicology in Vitro, 2023)

Tianwen-1 and MAVEN observations of Martian oxygen ion plumes - Xiao Ma; Anmin Tian; Ruilong Guo; Lihui Chai; Quanqi Shi; Shichen Bai; Qiugang Zong; Linggao Kong; Wenya Li; Binbin Tang; Aibing Zhang; Suiyan Fu; et al. (Icarus, 2023)

Structural variations in crocodile lizard populations provide novel insights into genomic variations in endangered animals - Lei Xiong; Zeshuo Zhou; Yi Song; Shichen Huang; Zhiyuan Li; Xuechi Zhu; Lei Xu; Xiangdong Kong; Yuxin Jiang (Molecular Ecology, 2023)
Population‐scale genome resequencing of endangered animals may contribute to gaining an understanding of how genomes vary as population sizes become smaller, as well as the functional implications of such variation. In this study, we analysed structural variations and gene presence and absence variations in the genomes of population of the endangered crocodile lizards. We found that the frequencies of some genes showed significant differences between crocodile lizards in different regions, indicating the influence of environmental selection, as well as potential contributions from demography and isolation, in shaping gene presence and absence variations. The haplotype diversity of major histocompatibility complex (MHC) genes was also found to differ among crocodile lizards inhabiting different regions. These findings indicate that well‐designed interbreeding of crocodile lizards from different regions may facilitate the exchange of genes between different lizard populations and increase the haplotype diversity of MHC genes, which may be beneficial for the survival of these lizards. Our findings in this study, based on differences in gene structural variation, provide new insights into genomic variation and may contribute to the conservation of endangered animals.

Prostate Cancer, Oxidative Stress, and Antioxidant Phytochemicals: A Brief Review - Shanyi Li; Tong Cai; Shichen Cui; Fangmin Liu; Rong Hu; Wenji Li (Current Pharmacology Reports, 2023)

Enhancing the anoxic/oxic process for treating hypersaline amide wastewater using a synthetic bacterial agent to regulate core bacterial interactions - Yanqing Zhang; Bin Liang; Xiaodan Ma; Jinglong Han; Zhiling Li; Shichen Nie; Ziyu Zhang; Aijie Wang (Journal of Water Process Engineering, 2023)

Environmental occurrence, risk, and removal strategies of pyrazolones: A critical review - Yanqing Zhang; Jingyuan Wang; Hanlin Cui; Shuhong Gao; Long Ye; Zhiling Li; Shichen Nie; Jinglong Han; Aijie Wang; Bin Liang (Journal of Hazardous Materials, 2023)

Highly efficient endosperm and pericarp protoplast preparation system for transient transformation of endosperm-related genes in wheat - Shichen Han; Ge Qu; Xiaohui Li; Feixiong Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Different Morphologies and Functional Nitrogen Accumulation Results in the Different Nitrogen Use Efficiency of Tobacco Plants - Shichen Li; Waqar Ahmed; Tao Zhang; Tao Jiang; Fupeng Mei; Qu Shan; Linyuan Yang; Cuilian Guo; Zhengxiong Zhao (Journal of Plant Growth Regulation, 2023)

Efficient removal of methylene blue from aqueous solution by ZIF-8-decorated helicoidal electrospun polymer strips - Shichen Li; Dhandayuthapani Thiyagarajan; Bong-Kee Lee (Chemosphere, 2023)

Identification for the species of aquatic higher plants in the Taihu Lake basin based on hyperspectral remote sensing - Shichen Mu; Kai You; Ting Song; Yajie Li; Lihong Wang; Junzhe Shi (Environmental Monitoring and Assessment, 2023)

Expandable polystyrene waste modified iron sludge-based biochar activating multiple free radicals for deep wastewater treatment - Shenglin Bu; Wenzong Liu; Muhammad Rizwan Haider; Xiqi Li; Wenzhe Zhang; Qi Sun; Qiandi Wang; Yuanqiang Guo; Shichen Nie; Aijie Wang (Process Safety and Environmental Protection, 2023)

Modulation of East Asian monsoon strength by ENSO during the warm periods of the late Holocene: Evidence from Porites corals in the northern South China Sea - Leilei Jiang; Kefu Yu; Shichen Tao; Wei Jiang; Shaopeng Wang; Yueer Li (Global and Planetary Change, 2023)

Tumor-derived microparticles-based nanomaterial as platform for delivery of tumor antigens to enhance immunogenicity - Qi Tan; Zimo Yang; Shichen Bu; Jiangbin Chen; Wenjuan Chen; Wei Geng; Qi Huang; Limin Duan; Mengfei Guo; Yali Wu; Jingjing Deng; E Zhou; et al. (Chemical Engineering Journal, 2023)

Acute Transcriptomic and Epigenetic Alterations at T12 After Rat T10 Spinal Cord Contusive Injury - Junkai Xie; Seth Herr; Donghan Ma; Shichen Wu; Han Zhao; Siyuan Sun; Zhixiong Ma; Matthew Yan-lok Chan; Katherine Li; Yang Yang; Fang Huang; Riyi Shi; et al. (Molecular Neurobiology, 2023)

A novel protein domain is important for photosystem II complex assembly and photoautotrophic growth in angiosperms - Wei Li; Jiangfan Guo; Xue Han; Xiaowen Da; Kai Wang; Hongfei Zhao; Shi-Tang Huang; Bosheng Li; Hang He; Ruirui Jiang; Shichen Zhou; Peng Yan; et al. (Molecular Plant, 2023)

Meridional response of Western North Pacific paleocyclone activity to tropical atmospheric circulation variability over the past millennium - Fei Tan; Yunfeng Zhang; Li Cao; Huilong Xu; Qi Shi; Xiyang Zhang; Shichen Tao; Jianxin Zhao; Hongqiang Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Efficient biodegradation of acetoacetanilide in hypersaline wastewater with a synthetic halotolerant bacterial consortium - Yanqing Zhang; Ke Shi; Hanlin Cui; Jinglong Han; Hao Wang; Xiaodan Ma; Zhiling Li; Ling Zhang; Shichen Nie; Changshui Ma; Aijie Wang; Bin Liang (Journal of Hazardous Materials, 2023)

Effects of regular addition and discontinuation of biosurfactant on hydrocarbon biodegradation and microorganisms in heavy oily sludge - Hanghai Zhou; Shichen Li; Lijia Jiang; Feng Zeng; Xiaoyun Lin; Chunlei Chen; Yanhong Li; Chunfang Zhang (Journal of Soils and Sediments, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Identification and molecular mapping of the semi-dwarf locus (sdf-1) in soybean by SLAF-seq method - Zhimin Dong; Liang Chen; Zhi Li; Nianxi Liu; Shichen Zhang; Jia Liu; Baoquan Liu (Euphytica, 2020)

Interaction between serine carboxypeptidase-like protein TtGS5 and Annexin D1 in developing seeds of Triticum timopheevi - Peihong Jiang; JianSheng Gao; Junyi Mu; Luning Duan; Yunsong Gu; Shichen Han; Lin Chen; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2020)

Analyzing the action of evolutionarily conserved modules on HMW-GS 1Ax1 promoter activity - Luning Duan; Shichen Han; Ke Wang; Peihong Jiang; Yunsong Gu; Lin Chen; Junyi Mu; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Molecular Biology, 2020)

Genome-wide identification of internal reference genes for normalization of gene expression values during endosperm development in wheat - Junyi Mu; Lin Chen; Yunsong Gu; Luning Duan; Shichen Han; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2019)

Analysis of synonymous codon usage of chloroplast genome in Porphyra umbilicalis - Guoling Li; Zonglian Pan; Shichen Gao; Yuyang He; Qiaoyu Xia; Yan Jin; Huipeng Yao (Genes & Genomics, 2019)

Comparative transcriptome analysis of salt-sensitive and salt-tolerant maize reveals potential mechanisms to enhance salt resistance - Mingquan Wang; Yufeng Wang; Yifei Zhang; Chunxia Li; Shichen Gong; Shuqin Yan; Guoliang Li; Guanghui Hu; Honglei Ren; Jianfei Yang; Tao Yu; Kejun Yang (Genes & Genomics, 2019)

Mapping novel aphid resistance QTL from wild soybean, Glycine soja 85-32 - Shichen Zhang; Zhongnan Zhang; Carmille Bales; Cuihua Gu; Chris DiFonzo; Ming Li; Qijian Song; Perry Cregan; Zhenyu Yang; Dechun Wang (Theoretical and Applied Genetics, 2017)

Interseasonal and interspecies diversities of Symbiodinium density and effective photochemical efficiency in five dominant reef coral species from Luhuitou fringing reef, northern South China Sea - Lijia Xu; Kefu Yu; Shu Li; Guohui Liu; Shichen Tao; Qi Shi; Tianran Chen; Huiling Zhang (Coral Reefs, 2017)